“HANGING OUT”, TRENDS IN SUBSTANCE USE AMONG YOUTH IN A PRIVATE TERTIARY INSTITUTION IN NIGERIA: A QUALITATIVE STUDY - Akingbade, Retta Ebi; Emmannuel, Oluwaseun Toluwase (PEOPLE: International Journal of Social Sciences, 2018)
Substance use among undergraduate students has intensified and is now considered a major public health problem in Nigeria. Majority of research on substance use has been quantitative and has not extensively considered the social context in which interactions occur. This study explored some critical social factors that might promote substance use among undergraduates in a private tertiary institution. The method was a cross sectional study conducted among thirty-one female and male students aged 17 – 27 years using FGDs, KIIS and IDIs. The instrument for the qualitative study was derived from the World Health Organization guidelines for substance use among students. Content analysis of five themes was interpreted, triangulating information from the various sources. Escalation of substance use was validated. Students’ preferred mode of fun and leisure was hanging out over a substance of choice and clubbing. Females preferred the use of psychoactive drugs while males preferred strong spirits and champagne. Abuse of cough syrup with codeine was very common among participants. Interestingly both male and female students reported that females surpass males in the use of substances. Female students were also more prone to sexual risk- taking behaviour than males. Students in their first and second year of studies engage more in the behaviour than students in their final year. Clubbing has increased considerably with students competing to outdo peers in buying the most expensive spirits and champagne. Movies, songs and musical videos glamourizing substance use were reported to have further reinforced the behaviour. Preventive strategies designed to increase self-esteem of students, assertiveness training to resist peer influence and programmes to increase youth’s knowledge and consequences of substance use is strongly recommended.